Acid and alkali resistant composite material, preparation method thereof and application of acid and alkali resistant composite material in solar photo-thermal water evaporation

MoO2/PTFE composite material is prepared by growing molybdenum dioxide spheres on hydrophilic PTFE film, which solves the problem of unstability of photothermal materials under acid and alkali conditions, and achieves wide spectrum absorption and stable water evaporation performance, which is suitable for solar photothermal water evaporation.

CN120329920APending Publication Date: 2025-07-18上海电气集团国控环球工程有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510662146.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing photothermal materials have strong absorption in the ultraviolet-visible light zone but weak near-infrared absorption, resulting in insufficient full spectrum utilization and unstable under acid and alkali conditions, making it difficult to apply to water evaporation at the solar photothermal interface.

Method used

Molybdenum dioxide spheres were grown on hydrophilic polytetrafluoroethylene film by solvent-thermal method, and MoO2/PTFE composite material was prepared, combined with the porous structure of the hydrophilic PTFE film to achieve wide spectrum absorption and chemical stability, and are suitable for water evaporation in harsh environments.

Benefits of technology

It realizes the stability and durability of the water evaporation rate in acid, alkali and high salt environments. The material is cheap and the production process is simple, and it is suitable for solar photothermal water evaporation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329920A_ABST
    Figure CN120329920A_ABST
Patent Text Reader

Abstract

The invention discloses an acid and alkali resistant composite material and a preparation method and application thereof in solar photo-thermal water evaporation, and belongs to the technical field of photo-thermal conversion materials, the key point of the technical scheme is that the preparation method of the acid and alkali resistant composite material comprises the following steps: S1, mixing pure water, ethanol and isopropanol to obtain a mixed solvent; s2, molybdenum acetylacetonate is dissolved in a mixed solvent to obtain a mixed solution; s3, the mixed solution and a hydrophilic PTFE film are mixed and then heated for 8-12 h at the temperature of 180-220 DEG C, and the MoO2 / PTFE composite material is prepared, molybdenum dioxide balls grow on the hydrophilic PTFE film through a solvothermal method, the water evaporation rate of the composite material can be kept stable in the severe environment (acidic, alkaline or high-salt), and therefore the composite material shows excellent stability and durability, and the composite material can be used for preparing the composite material. In addition, the used materials are low in price, the manufacturing process is simple, and popularization is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photothermal conversion materials, and particularly to an acid and alkali resistant composite material, a preparation method thereof, and an application in solar photothermal water evaporation. Background Art

[0002] Solar energy is a sustainable, environmentally friendly and cost-effective clean energy. Solar-driven water evaporation technology, with its characteristic of absorbing sunlight and converting it into heat energy, shows good development prospects in the fields of wastewater treatment and seawater desalination. Compared with the traditional bulk water heating method, solar interfacial water evaporation uses a solar absorber floating on the water surface to transfer heat to the water-air interface, with higher energy conversion efficiency.

[0003] Efficient solar-steam conversion usually depends on photothermal materials. The design and utilization of photothermal materials are prerequisite steps for effectively providing an interfacial solar evaporator. Currently, common photothermal materials include carbon-based materials, semiconductor materials, plasma materials, etc. However, carbon-based materials have strong absorption in the ultraviolet-visible light region but weak absorption in the near-infrared region, resulting in insufficient full-spectrum utilization; most plasma materials are expensive (such as noble metals) or unstable under acid-base conditions; semiconductor materials, with their chemical stability and abundant natural resources, are considered one of the most promising photothermal conversion materials. Molybdenum dioxide in semiconductor materials has been widely used in fields such as photothermal therapy and surface-enhanced Raman spectroscopy. Molybdenum dioxide (MoO2) has the characteristics of antioxidation and acid and alkali corrosion resistance, and is very competitive in photothermal conversion materials. However, there is currently no good carrier to enable the application of molybdenum dioxide in solar photothermal interfacial water evaporation. Summary of the Invention

[0004] In order to solve the problems in the prior art, the present invention provides an acid and alkali resistant composite material, a preparation method thereof, and an application in solar photothermal water evaporation. In this application, molybdenum dioxide spheres are grown on a hydrophilic polytetrafluoroethylene membrane by a solvothermal method. The composite material can maintain a stable water evaporation rate under harsh environments (acidic, alkaline or high-salt), thereby showing excellent stability and durability. Moreover, the materials used in the present invention are cheap, the manufacturing process is simple, and it is easy to promote.

[0005] The first aspect of the present invention is to provide a preparation method of an acid and alkali resistant composite material, adopting the following technical scheme: A preparation method of an acid and alkali resistant composite material, comprising the following steps: S1. Mix pure water, ethanol and isopropanol to obtain a mixed solvent; S2. Dissolve molybdenum acetylacetonate in the mixed solvent to obtain a mixed solution; S3. Mix the mixed solution with the hydrophilic PTFE membrane and heat it at 180 - 220 °C for 8 - 12 h to obtain the MoO₂ / PTFE composite material.

[0006] By adopting the above technical solution, in the present invention, molybdenum dioxide spheres are grown on the hydrophilic PTFE membrane through a solvothermal method to obtain a solar composite membrane that can exhibit good durability in harsh environments. Molybdenum dioxide has a wide - spectrum absorption ability, and its absorption properties can remain stable under acidic, alkaline, and heating conditions. The hydrophilic PTFE membrane has a porous structure and good chemical stability, which is conducive to water transmission and vapor diffusion. Therefore, after the molybdenum dioxide and the hydrophilic PTFE membrane are compounded, in harsh environments (acidic, alkaline, or high - salt), the water evaporation rate of the composite membrane can remain stable, showing excellent stability and durability. Moreover, the raw materials used in the present invention are cheap, the manufacturing process is simple, and it is easy to promote.

[0007] In a preferred embodiment, the volume ratio of pure water to ethanol and isopropanol is 1:1:(2 - 5).

[0008] By adopting the above technical solution, when the volume ratio of pure water, ethanol, and isopropanol is controlled within this range, it can effectively enable molybdenum dioxide spheres to grow on the hydrophilic PTFE membrane, ensuring the loading amount of molybdenum dioxide spheres on the hydrophilic PTFE membrane, thereby ensuring the quality of the composite material formation.

[0009] In a preferred embodiment, the weight ratio of molybdenum acetylacetonate to the hydrophilic PTFE membrane is (15 - 60):8.

[0010] By adopting the above technical solution, when the ratio of molybdenum acetylacetonate to the hydrophilic PTFE membrane is within this range, it can ensure the loading amount of molybdenum dioxide on the hydrophilic PTFE membrane, thereby keeping the thickness of the membrane within a certain range. When the content of molybdenum acetylacetonate is too high, the loading amount of molybdenum dioxide on the hydrophilic PTFE membrane is too high, resulting in too high a thickness of the finally obtained composite membrane, thus affecting the flexibility of the composite membrane. On the contrary, when the content of molybdenum acetylacetonate is too low, the thickness of the composite membrane is too thin, the strength of the composite membrane is relatively poor, and the light conversion efficiency is also low. Therefore, when the two are controlled within this range, it can effectively ensure the mechanical properties and light conversion properties of the composite membrane.

[0011] In a preferred embodiment, the diameter of the hydrophilic PTFE membrane is 25 mm and the pore diameter is 0.22 μm.

[0012] The second aspect of the present invention is to provide an acid - and alkali - resistant composite material prepared by the preparation method of the acid - and alkali - resistant composite material as described above.

[0013] The third aspect of the present invention is to provide an application of the acid and alkali resistant composite material as described above in solar photo-thermal water evaporation, including the following steps: soaking the acid and alkali resistant composite material in a n-hexane solution containing polydimethylsiloxane for 2 - 3 s, and then drying it in an oven at 60 ± 1 °C to obtain a composite membrane for water evaporation and water quality purification experiments.

[0014] In a preferred embodiment, the concentration of polydimethylsiloxane in the n-hexane solution is 15 wt%.

[0015] In a preferred embodiment, the light absorption rate of the composite membrane in the wavelength range of 400 - 2000 nm is 92 - 95%.

[0016] In summary, the present invention has the following beneficial effects: By means of a solvothermal method, molybdenum dioxide spheres are grown on a hydrophilic PTFE membrane to prepare a solar composite membrane that can exhibit good durability in harsh environments. Molybdenum dioxide has a wide spectral absorption ability, and its absorption properties can remain stable under acidic, alkaline, and heating conditions. The hydrophilic PTFE membrane has a porous structure and good chemical stability, which is conducive to water transport and vapor diffusion. Therefore, after the molybdenum dioxide and the hydrophilic PTFE membrane are combined, in harsh environments (acidic, alkaline, or high salt), the water evaporation rate of the composite membrane can remain stable, showing excellent stability and durability. Moreover, the raw materials used in the present invention are cheap, the manufacturing process is simple, and it is easy to promote. Description of the Drawings

[0017] Figure 1 It is a scanning electron microscope image (SEM) of the composite material obtained in Application Example 1 of the present application.

[0018] Figure 2 It is a graph of the optical absorption detection results of the membranes in Application Example 1 and Application Comparative Example 1 of the present application.

[0019] Figure 3 It is a graph of the change of temperature with time under light of the membranes in Application Example 1 and Application Comparative Example 1 of the present application.

[0020] Figure 4 It is the water evaporation rate of the membranes in Application Example 1 and Application Comparative Example 1 of the present application in water, solutions with pH = 1, and pH = 14.

[0021] Figure 5 It is a graph of the change of ion concentration in the seawater desalination test of the membrane obtained in Application Example of the present application. Detailed Description of the Embodiments

[0022] The following further details the present invention with reference to the accompanying drawings. All reagents not indicating the manufacturer can be conventional reagent products obtained through commercial purchase. Example 1

[0023] A preparation method of an acid and alkali resistant composite material, comprising the following steps: S1. Mix pure water, ethanol and isopropanol in a volume ratio of 1:1:2 to obtain a mixed solvent, that is, take 9 mL of pure water, 9 mL of ethanol and 27 mL of isopropanol; S2. Add 150 mg of molybdenum acetylacetonate to the mixed solvent, and stir and dissolve at room temperature for 2 h to obtain a mixed solution; S3. Transfer the mixed solution to a 50 mL Teflon stainless steel reaction kettle, put in an 80 mg hydrophilic PTFE membrane (with a diameter of 25 mm and a pore size of 0.22 μm), mix, and heat in an oven at 200 °C for 10 h to obtain the MoO2 / PTFE composite material. Example 2

[0024] A preparation method of an acid and alkali resistant composite material, comprising the following steps: S1. Mix pure water, ethanol and isopropanol in a volume ratio of 1:1:3 to obtain a mixed solvent, that is, take 9 mL of pure water, 9 mL of ethanol and 18 mL of isopropanol; S2. Add 150 mg of molybdenum acetylacetonate to the mixed solvent, and stir and dissolve at room temperature for 2 h to obtain a mixed solution; S3. Transfer the mixed solution to a 50 mL Teflon stainless steel reaction kettle, put in a 70 mg hydrophilic PTFE membrane (with a diameter of 25 mm and a pore size of 0.22 μm), mix, and heat in an oven at 180 °C for 10 h to obtain the MoO2 / PTFE composite material. Example 3

[0025] A preparation method of an acid and alkali resistant composite material, comprising the following steps: S1. Mix pure water, ethanol and isopropanol in a volume ratio of 1:1:5 to obtain a mixed solvent, that is, take 9 mL of pure water, 9 mL of ethanol and 18 mL of isopropanol; S2. Add 150 mg of molybdenum acetylacetonate to the mixed solvent, and stir and dissolve at room temperature for 2 h to obtain a mixed solution; S3. Transfer the mixed solution to a 50 mL Teflon stainless steel reaction kettle, put in an 80 mg hydrophilic PTFE membrane (with a diameter of 25 mm and a pore size of 0.22 μm), mix, and heat in an oven at 220 °C for 8 h to obtain the MoO2 / PTFE composite material. Example 4

[0026] A preparation method of an acid and alkali resistant composite material, which is different from Example 1 in that the amount of molybdenum acetylacetonate used is 300 mg, and the others are the same as in Example 1. Example 5

[0027] A preparation method of an acid and alkali resistant composite material, which is different from Example 1 in that the dosage of molybdenum acetylacetonate is 600 mg, and the others are the same as in Example 1. Example 6

[0028] A preparation method of an acid and alkali resistant composite material, which is different from Example 1 in that the dosage of molybdenum acetylacetonate is 700 mg, and the others are the same as in Example 1. Example 7

[0029] A preparation method of an acid and alkali resistant composite material, which is different from Example 1 in that the dosage of molybdenum acetylacetonate is 100 mg, and the others are the same as in Example 1. Application Examples 1-7

[0030] The composite material prepared in the above examples was immersed in a 15 wt% n-hexane solution containing polydimethylsiloxane for 2 s, and then dried in an oven at 60 °C to obtain a composite membrane for water evaporation and water purification experiments.

[0031] The electron scanning microscope image of the composite membrane obtained in Application Example 1 is as Figure 1 shown. Molybdenum dioxide nanospheres grow on the surface of the PTFE membrane, and the surface of the membrane is in a loose and porous state; the electron scanning microscope images of the composite membranes obtained in Application Examples 2-5 are basically the same as those in Figure 1 , and the surface of the membrane is in a loose and porous state; the thickness of the composite membrane obtained in Application Example 6 is much thicker than that of the composite membrane obtained in Application Example 1. The composite membrane is relatively hard, and the amount of pores on the membrane surface in the scanning electron microscope is greatly reduced and the pore diameter is smaller; the thickness of the composite membrane obtained in Application Example 7 is much smaller than that of the composite membrane obtained in Application Example 1. The composite membrane is too thin, and the pore diameter on the membrane surface is larger. Application Comparative Example 1

[0032] The hydrophilic PTFE membrane was immersed in a 15 wt% n-hexane solution containing polydimethylsiloxane for 2 s, and then dried in an oven at 60 °C to obtain a PTFE membrane for water evaporation and water purification experiments. Performance Test

[0033] The composite membranes obtained in Application Example 1 and Application Comparative Example 1 for water evaporation and water purification experiments were tested for light absorption rate, photothermal conversion performance, water evaporation performance, and seawater desalination test, as follows: (1) The composite membrane obtained in Application Example 1 was subjected to optical absorption test, and the test results are as Figure 2 shown. Its light absorption rate in the wavelength range of 400-2000 nm is about 92-95%.

[0034] After the PTFE membrane in Application Comparative Example 1 was subjected to optical absorption test, the test results are as Figure 2As shown, the light absorption rate of light with a wavelength in the range of 400 - 2000 nm is approximately 10 - 23%.

[0035] (2)During the photothermal conversion test, the composite film obtained from the application example was placed in a beaker filled with water. The light intensity of the xenon light source was adjusted to 1 kW / m2, and the temperature change on the surface of the composite film was monitored by an infrared thermal imager. After irradiation for 1200 s, the temperature on the surface of the composite film increased to 40 °C, as Figure 3 shown, indicating a fast photothermal conversion rate.

[0036] The composite film obtained from Comparative Control Example 1 was placed in a beaker filled with water. The light intensity of the xenon light source was adjusted to 1 kW / m2, and the temperature change on the surface of the composite film was monitored by an infrared thermal imager. After irradiation for 1200 s, the temperature on the surface of the composite film increased to 29 °C, as Figure 3 shown. Compared with Application Example 1, its photothermal conversion efficiency is very slow.

[0037] (3)Water evaporation performance test: The composite film obtained from Application Example 1 and the PTFE film of Application Comparative Example 1 were respectively placed in water, solutions with pH = 1, and pH = 14. The water evaporation rate was measured when the intensity of the xenon light source was 1 kW / m 2 . The test results are as Figure 4 shown. It can be seen from Figure 4 that the water evaporation rate of the composite film obtained from Application Example 1 can remain stable in the three solutions, and the water evaporation rates are all much higher than those of the PTFE film of Application Comparative Example 1, indicating that the acidity and alkalinity of the solution do not have an obvious effect on the water evaporation rate of the composite film, indicating that the composite film obtained from Application Example 1 of this application has the effect of acid and alkali resistance, and at the same time indicating that the composite film obtained from this application has broad applicability for use in different future environments.

[0038] (4)In the simulated seawater desalination experiment, a seawater desalination simulation experiment was carried out using the sea water of the Yellow Sea. The composite film obtained from Application Example 1 and the PTFE film of Application Comparative Example 1 were tested. The change in the ion concentration in the water before and after membrane treatment was determined by ICP - AES. The test results are as Figure 5 shown. It can be seen from Figure 5 that after treating the seawater with the composite film obtained from Application Example 1, the sodium ions, potassium ions, calcium ions, and magnesium ions in the seawater all decreased significantly, indicating that the composite film obtained from this application can be applied to the seawater desalination experiment and can achieve significant effects.

[0039] The optical absorption rate, photothermal conversion efficiency, water evaporation performance, and seawater desalination effect of the composite film obtained in Application Example 2-5 are basically similar to the test results in Application Example 1, so no separate drawings are provided. For Application Examples 6-7, since the scanning electron microscope images are quite different from those in Application Example 1, it can be predicted that their optical absorption rate, photothermal conversion efficiency, water evaporation performance, and seawater desalination effect are all worse than those in Application Example 1.

[0040] The embodiments of this specific implementation manner are all preferred embodiments of the present invention, and do not limit the protection scope of the present invention accordingly. Therefore, all equivalent changes made according to the structure, shape, and principle of the present invention shall be covered within the protection scope of the present invention.

Claims

1. A preparation method of an acid and alkali resistant composite material, characterized in that: It includes the following steps: S1. Mix pure water, ethanol and isopropanol to obtain a mixed solvent; S2. Dissolve molybdenum acetylacetonate in the mixed solvent to obtain a mixed solution; S3. Mix the mixed solution with a hydrophilic PTFE membrane and heat at 180 - 220 °C for 8 - 12 h to obtain a MoO₂ / PTFE composite material.

2. The preparation method of an acid and alkali resistant composite material according to claim 1, characterized in that: The volume ratio of the pure water to ethanol and isopropanol is 1:1:(2 - 5).

3. The preparation method of an acid and alkali resistant composite material according to claim 1, characterized in that: The weight ratio of the molybdenum acetylacetonate to the hydrophilic PTFE membrane is (15 - 60):

8.

4. The preparation method of an acid and alkali resistant composite material according to claim 1, characterized in that: The diameter of the hydrophilic PTFE membrane is 25 mm and the pore size is 0.22 μm.

5. An acid and alkali resistant composite material prepared by the preparation method of the acid and alkali resistant composite material according to any one of claims 1 - 4.

6. Use of the acid- and alkali-resistant composite material as described in claim 5 in solar photo-thermal water evaporation, characterized in that: It includes the following steps: Immerse the acid and alkali resistant composite material in a n - hexane solution containing polydimethylsiloxane for 2 - 3 s, and then place it in an oven at 60 ± 1 °C to dry to obtain a composite membrane for water evaporation and water quality purification experiments.

7. The application according to claim 6, wherein: The concentration of the polydimethylsiloxane in the n - hexane solution is 15 wt%.

8. The application according to claim 6, characterized in that: The light absorption rate of the composite membrane in the wavelength range of 400 - 2000 nm is 92 - 95%.